Photocatalytic Performance of Anion Doped TiO2 on the Degradation of Complex Organic Matrix - Birben, Nazmiye Cemre; Uyguner-Demirel, Ceyda Senem; Sen-Kavurmaci, Sibel; Gurkan, Yelda Yalcin; Turkten, Nazli; Kilic, Murat; Cinar, Zekiye; Bekbolet, Miray (SYCAMORE GLOBAL PUBLICATIONS LLC, 2016)
TiO2 photocatalysis has gained a great interest as an innovative and effective treatment process for the removal of complex organic matter present in water and wastewater. Employment of TiO2 as a photocatalyst has its limitations due to its wide band gap that causes utilization of very small fraction of solar light. In that respect, structural modifications of TiO2, such as metal and non-metal doping have been revealed in detail to benefit from solar radiation for photocatalytic applications. In this study, photocatalytic performances of C-doped, N-doped, S-doped and S-N co-doped TiO2 photocatalysts were investigated for the degradation of a high molecular size fraction of humic acid as a representative of complex organic matrix. For this purpose, 100 kDa molecular size fraction of humic acid solution was subjected to both solar (Solar/PC) and UV (UV/PC) photocatalytic oxidation processes. Degradation kinetics and removal percentages were comparatively evaluated in terms of humic UV-vis parameters (Color436 and UV254) and dissolved organic carbon contents. Moreover, advanced fluorescence techniques in the form of an excitation-emission matrix (EEM) of fluorescence intensity as a function of excitation and emission wavelengths were also applied. Comparison of the photocatalytic removal efficiencies of different anion doped TiO2 specimens revealed higher performance of solar photocatalytic oxidation process in terms of the selected humic parameters. EEM fluorescence features displayed the removal of humic-like fluorophores and emergence of fulvic-like fluorophores in accordance with removal extent of dissolved organic carbon contents which could be attributed to the performances of anion doped TiO2 specimens as S-N co-doped>N-doped>C-doped>S-doped>bare for UV/PC process.
Keywords: Anion doped TiO2; EEM fluorescence; humic acids; UV and solar photocatalytic degradation; VISIBLE-LIGHT; TITANIUM-DIOXIDE; NITROGEN; SULFUR; REMEDIATION; OXIDATION; Chemistry